Illegitimate patients: Undocumented immigrants' access to health care in Chile - Nanette Paz Liberona Concha; Miguel Angel Mansilla (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2017)
In recent decades, Chile has become a destination for immigrants from other South American countries, which has significantly impacted public services - particularly the public health system - at the economic, social, and cultural levels. The aim of this paper is to provide substantiated information on issues concerning undocumented immigrants' access to health care in Chile. A qualitative methodology, fundamentally an ethnography of the clinical setting, was used. Results were then analyzed in relation to theories of power asymmetries and interethnic relations. The research results highlight the lack of compliance with existing regulations and the exercise of discretionary personal judgment as barriers to access. It is concluded that in Chile immigrants in general, and undocumented immigrants in particular, are considered to be illegitimate patients.